Type II Anion Relay Chemistry: Exploiting Bifunctional Weinreb Amide Linchpins for the One‐Pot Synthesis of Differentiated 1, 3‐Diketones, Pyrans, and Spiroketals. (20th November 2015) - Farrell, Mark; Melillo, Bruno; Smith, Amos B.
Abstract: The design, synthesis, and validation of new highly effective bifunctional linchpins for type II anion relay chemistry (ARC) has been achieved. The mechanistically novel negative‐charge migration that comprises the Brook rearrangement is now initiated by a stabilized tetrahedral intermediate, which is generated by nucleophilic addition to a Weinreb amide, rather than by a simple oxyanion that is generated from an epoxide. As a result, the linchpin preserves the carbonyl functionality in the ARC adducts, thus permitting access to functionally complex systems in a single flask without the need for further chemical manipulations. This tactic was validated with the one‐pot preparation of monoprotected 1, 3‐diketones as well as pyran and spiroketal scaffolds, depending on the choice of nucleophile, electrophile, and work‐up conditions.